JavaScript : the complete reference - Powell, Thomas A.; Fritz Schneider (New York : McGraw Hill Education, 2012)
Design, debug, and publish high-performance web pages and applications using tested techniques and best practices from expert developers. The all-new edition of this comprehensive guide has been thoroughly revised and expanded to cover the latest JavaScript features, tools, and programming methods. JavaScript: The Complete Reference, Third Edition provides illustrative examples, line-by-line code samples, and practical development advice$1 (Bfrom the core of the language to the various standard and emerging APIs supported by modern web browsers. This in-depth resource covers everything you need to know, whether you$1 (Bre trying to understand the fundamentals of weak typing in JavaScript, reduce your confusion over closures, or perform common tasks like form validation or Ajax calls.s
Chapter 1. Introduction to JavaScript; Chapter 2. JavaScript Core Features; Chapter 3. Data Types & Variables; Chapter 4. Operators, Expressions & Statements; Chapter 5. Functions; Chapter 6. Objects; Chapter 7. Array, Date, Math; Chapter 8. Regular Expressions; Chapter 9. JavaScript Object Models; Chapter 10. The Standard DOM; Chapter 11. Event Handling; Chapter 12. Cnt. Windows & Frames; Chapter 13. Handling Documents; Chapter 14. Form Handling; Chapter 15. DHTML and Beyond; Chapter 16. Canvas; Chapter 17. JavaScript UIs; Chapter 18. Browser Detection; Chapter 19. Cookies & Persistence; Chapter 20. JS & Embedded Objects; Chapter 21. Ajax and Remote JS; Chapter 22. JavaScript and XML; Chapter 23. Browser Specific JS; Chapter 24. JavaScript Security; Chapter 25. JavaScript Practices
Keywords: JAVASCRIPT (CMPUTER PROGRAM LANGUAGE)